PEMANFAATAN WARUNG KOPI SEBAGAI RUANG PUBLIK DI KOTA BANDA ACEH - , EKA OCTA FIRMANSYAH, Widyasari Her Nugrahandika, ST.,M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Aceh is specialized in high quality coffee comodity in the world. Therefore, Aceh becomes the top arabica coffee producer in Indonesia. Morover, Aceh is also known as a province of thousands coffee shops. This expression is born since numerous coffee shops are continuosly emerging. One of the city where many coffee shops emerge is Banda Aceh. Among the society of Banda aceh, coffee shop is an important public place to do many activity. The existence of the coffee shop also fullfill many things that canât be found within coffee shop itself. This research is focused to verify the utilization of coffee shop by observing how it becomes a public space in Banda Aceh. Public space is also defined as a place used by the public for any kind of activity without being segmented by social and economical background of its users. Therefore, a good public space is needed by the people to discuss, learn, inspire, inform, and even negotiate in occupational context. This research uses deductive approach method with descriptive analysis method. The verification of the utilization of coffee shop as public space is counducted by using 5 research variables